Accidentally Found Morgagni Hernia in Adult: Case Report - Dineva, Stoyanka; Veleva, Iliyana; Pavlova, Adelina; Todorov, Deyan (International Journal For Research In Health Sciences And Nursing, 2017)
Adult onset diaphragmatic hernia is a rare condition with variable clinical manifestations. The majority of adult-onset diaphragmatic hernia is associated with trauma. Blunt thoracic and abdominal trauma associated with a 5% to 7% incidence of diaphragmatic injury, and in 3% to 15% for those with penetrating injury. In this report, we describe the case of an adult patient who had a rightsided diaphragmatic hernia but no history of trauma. Diaphragmatic hernia usually occurs in the posterolateral portion of the diaphragm (Bochdalek hernia) and is on the left side in 90% of cases; in 2% of cases it is bilateral. The estimated incidence is 1 to 4 in 10 000 live births. Anterior hernias (Morgagni hernia) are far less common.